Analisis Struktur Naratif dalam Cerita Rakyat Hikayat Lehamik (Manusia Raksasa Rote) - Kristina Rejoice Malelak Belan; Marselus Robot; Margareta P.E Djokaho (YASIN, 2026)
Although Hikayat Lehamik (The Giant Man of Rote) features a distinctive plot, characterization, and local cultural symbols that represent the worldview of the Rote community, academic studies revealing the narrative structure of this folktale through a narratological approach remain limited. This study aims to describe the narrative structure of Hikayat Lehamik based on Seymour Chatman’s narratological theory. This study employed a qualitative descriptive method using textual analysis of the folktale, which was sourced from an online text adapted by Gyanto. The data were collected through critical reading and note-taking using coding cards and were then classified based on sequences, kernels, satellites, characters, settings, and the relationship between story and discourse. The findings show that the narrative structure of Hikayat Lehamik is organized linearly through a chronological forward-moving plot and clear causal relationships. The story consists of six sequences, three kernels, and three satellites that mutually support the development of the conflict through to its resolution. Lehamik is portrayed as an innocent main character, the community functions as a collective character driven by fear, while Lehamik’s wife serves as the catalyst for the development of the conflict. The spatial, temporal, and social settings reinforce the meaning of the story while representing the culture of the Rote community. This study concludes that the elements of events and existents form a coherent narrative structure and convey a message concerning the consequences of fear, prejudice, and collective decisions that are not grounded in justice. The findings of this study contribute to the development of oral literature studies, support the teaching of regional literature, and strengthen efforts to preserve folktales as part of the cultural heritage of the Rote community.